Yi Lacquerware Artistic Characteristics of Modern Art Design Applications - Zhao, Qiqi; Wan Jamarul Imran, Wan Abdullah Thani (Paradigm Academic Press, 2024)
This article delves into the cultural background and artistic elements of Yi lacquerware, exploring their integration with modern art design concepts to underscore the imperative of preserving Yi lacquerware in today’s society. The focus lies on innovatively blending the visual aspects of traditional Yi handicrafts into contemporary art design, ensuring the retention of Yi cultural characteristics while addressing modern aesthetic and functional requirements. Through a detailed examination of the application of Yi lacquerware’s artistic attributes in modern design, the article derives pertinent design strategies that serve as a dual legacy — preserving traditional ethnic culture and offering a substantial contribution to the realm of contemporary art.